Love in the library - Tokuda-Hall, Maggie (Candlewick Press, 2022)
"To fall in love is already a gift. But to fall in love in a place like Minidoka, a place built to make people feel like they weren't human -- that was miraculous. After the bombing of Pearl Harbor, Tama is sent to live in a War Relocation Center in the desert. All Japanese Americans from the West Coast -- elderly people, children, babies -- now live in prison camps like Minidoka. To be who she is has become a crime, it seems, and Tama doesn't know when or if she will ever leave. Trying not to think of the life she once had, she works in the camp's tiny library, taking solace in pages bursting with color and light, love and fairness. And she isn't the only one. George waits each morning by the door, his arms piled with books checked out the day before. As their friendship grows, Tama wonders: Can anyone possibly read so much? Is she the reason George comes to the library every day? Beautifully illustrated and complete with an afterword, back matter, and a photo of the real Tama and George -- the author's grandparents -- Maggie Tokuda-Hall's elegant love story for readers of all ages sheds light on a shameful chapter of American history."-- Provided by publisher.